2004
DOI: 10.1016/j.otohns.2004.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Predictors of Occult Neck Metastasis in Early Oral Tongue Cancer

Abstract: The clinical and histopathologic factors studied herein permit greater selectivity and more informed decision-making than does presurgical evaluation, when addressing elective neck treatment for early N0 oral tongue cancer. The multivariate model derived from this study appears to be a more reliable method for determining the patients most likely to benefit from elective neck dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
129
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(141 citation statements)
references
References 17 publications
10
129
2
Order By: Relevance
“…In our study there was no correlation between lymphovascular and perinueral invasion and neck metastasis but other studies have found them to be independent predictors [16,20].…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…In our study there was no correlation between lymphovascular and perinueral invasion and neck metastasis but other studies have found them to be independent predictors [16,20].…”
Section: Discussioncontrasting
confidence: 91%
“…Byers et al found that an increasing tumor grade predicted lymph node metastasis (odd ratio2.40) [15]. Sparano et al and Lim et al also showed positive correlation between grade of the tumor and lymph node metastasis [16,17].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Many histo-pathologic features have been previously investigated as risk factors for occult cervical lymph node metastasis in early OTC but there is no consensus [9,10,18] and there is still controversy regarding the management of clinical N0 neck [19]. The PVI and PLI are identified as the factors of RR but no statistical difference in DFS or OS between elective treatment and observation groups in the present study.…”
Section: Discussionmentioning
confidence: 48%
“…Early tongue and oral floor cancer is known for its propensity for subclinical lymph node metastasis, and the incidence of late neck metastasis has been reported at 20-30% 2,3,4 . It has been reported 5,6 that patients with neck lymph node metastasis tend to develop distant metastasis, even though the regional control is maintained by neck dissection.…”
Section: Introductionmentioning
confidence: 99%